2020
DOI: 10.1177/0959651820965406
|View full text |Cite
|
Sign up to set email alerts
|

State-of-charge estimation based on model-adaptive Kalman filters

Abstract: This article presents a set of algorithms for the estimation of state of charge, specifically deployed for lithium-ion batteries. These algorithms are based on appropriate battery models. These models can be developed having different levels of accuracy, also including the possibility to correctly represent the hysteresis voltage behaviour of the selected lithium cells. In addition, different identification methods of the battery model parameters may also be considered, considering tabulated parameters, calibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Researches have shown that factors such as temperature, charge/discharge rate have a great influence on battery life. Pugi and coauthors 22 presented a set of algorithms utilizing the nonlinear Kalman filter for estimating the battery SOC. Wang 23 developed a semi-empirical model to describe the life loss of Li-ion batteries based on experimental data, but this model is limited to specific charge/discharge conditions (e.g.…”
Section: Vehicle Modelsmentioning
confidence: 99%
“…Researches have shown that factors such as temperature, charge/discharge rate have a great influence on battery life. Pugi and coauthors 22 presented a set of algorithms utilizing the nonlinear Kalman filter for estimating the battery SOC. Wang 23 developed a semi-empirical model to describe the life loss of Li-ion batteries based on experimental data, but this model is limited to specific charge/discharge conditions (e.g.…”
Section: Vehicle Modelsmentioning
confidence: 99%
“…In the article, the forgetting factor algorithm is introduced to improve the accuracy of parameter identification and then improve the estimation accuracy. The equation of state for the system is shown in Equation (8).…”
Section: Soc and Soh Joint Estimation Based On Forgetting Factor Dual...mentioning
confidence: 99%
“…SOC can directly reflect the remaining power of the battery, which is a significant parameter to reflect the state of the battery 7 . For the estimation, the main methods taken advantage of are the ampere‐hour integration, 8 open‐circuit voltage (OCV), Kalman filter, and neural network methods 9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The economy is another very important aspect that will determine whether they can survive in the market competition. Meanwhile, the real-time and accurate estimation of the state of charge (SOC) of the battery would have an impact on the economy of the hybrid electric vehicle [33,34]. Notwithstanding, considering the significant importance and wide range of applications, many challenges remain incapable in applications and cognizance to characterization and battery managements for lithium-ion battery technology [35].…”
Section: Introductionmentioning
confidence: 99%